Electronic Sunflower Design - Chen, Peng (Journal of Theory and Practice of Engineering Science, 2024)
Solar energy is known as the most primitive source of energy; it's clean, renewable, abundant, and widely distributed, offering a very broad prospect for utilization. However, the low efficiency of solar energy utilization has always been affecting and hindering the popularization of solar energy technology. The design of a solar tracking system offers a new approach to solving this problem, thereby greatly improving the efficiency of solar energy utilization. This design employs a photoelectric tracking method, using a stepper motor driven by photoelectric sensors, which generate feedback signals to a microprocessor based on the intensity of incident light. The microprocessor runs the program and controls the tracking mechanism to adjust the angle of the solar panels to track the sun. A single-chip microcontroller-implemented solar tracking system can effectively improve the photoelectric conversion efficiency of solar panels and has a broad application prospect.